Distributed Health Literacy in the Maternal Health Context in Vietnam - Shannon McKinn; Duong Thuy Linh; Kirsty Foster; Kirsten McCaffery (SLACK Incorporated, 2019)
Background: Previous health literacy research has often focused on individual functional health literacy, ignoring the cultural contexts through which many people experience health care. Objective: We aimed to explore the nature of maternal health literacy among ethnic minority women in a low-resource setting in Vietnam. Methods: Using a qualitative approach, we conducted focus groups with 42 pregnant women, mothers, and grandmothers of children younger than age 5 years from the Thai and Hmong ethnic groups. Semi-structured interviews were conducted with key informants and thematic analysis was performed. Key Results: The findings of our thematic analysis aligned well with the concept of distributed health literacy. We found that ethnic minority women drew upon family and social networks of health literacy mediators to share knowledge and understanding, assess and evaluate information, communicate with health professionals, and support decision-making. Family members were also involved in making health decisions that had the potential to negatively affect women and children's health. Conclusions: Family members are an important source of information for ethnic minority women, and they influence decision-making. Relatives and husbands of pregnant women could be included in maternal health education programs to potentially strengthen the health literacy of the whole community. The distributed health literacy concept can be used to strengthen health promotion messages and to reduce the risk of negative health outcomes.